Vivero Centroamericano de Adaptacion y Rendimiento VICAR 1983 y 1984 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
The results of the 1983 A and B and 1984 A and B Central American bean yield and adaptation nursery (VICAR) are presented. The nurseries were classified into red and black beans. The red bean 1983 A and B nurseries, composed of 12 materials and a control, were planted at 2 sites in Costa Rica, 2 in El Salvador, 5 in Nicaragua, and 4 in Honduras; yield results are detailed for 6 sites. The black bean 1983 A and B nurseries, composed of 15 materials and a control, were planted at 2 sites in Guatemala, 2 in Costa Rica, 2 in El Salvador, 4 in Honduras, and 5 in Nicaragua; yield results are detailed for 7 sites. The yields of the red bean 1984 A and B nurseries, composed of 15 materials and a control, are reported for 6 and 8 sites, resp. The reactions of the materials in the 1984 red and black nurseries to Uromyces phaseoli, Thanatephorus cucumeris, Xanthomonas phaseoli, and Isariopsis griseola are presented. (CIAT)